2022
DOI: 10.3389/fcimb.2022.941860
|View full text |Cite
|
Sign up to set email alerts
|

In and out: Leishmania metastasis by hijacking lymphatic system and migrating immune cells

Abstract: The lymphatic system plays a crucial role in mounting immune response against intracellular pathogens, and recent studies have documented its role in facilitating tumor dissemination linked largely with cancer cells. However, in mucocutaneous leishmaniasis (MCL) caused by Leishmania Viannia subgenus showing infectious metastasis and resulting in severe distant secondary lesions, the route of escape of these parasites to secondary sites has not yet been investigated in detail. Our results demonstrated that when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The only report currently available on in-vivo quiescence in the context of chemotherapy revealed, in miltefosine-treated L. mexicana -infected BALB/c mice, the presence of quiescent amastigotes in collagen-rich, dermal mesothelium surrounding granulomas ( Kloehn et al., 2021 ): the authors concluded that quiescence, together with the lack of miltefosine accumulation in the mesothelium, may contribute to drug failure and non-sterile cure. The potential for DT and persistence shown here by L. braziliensis strains and by L. lainsoni ( Jara et al., 2022 ) might explain several (sub)clinical features associated with the species of subgenus Viannia , like i) the presence of parasites in 80% of scars, years after treatment with pentavalent antimony therapy ( Schubach et al., 1998 ); ii) the mucosal metastases from healed primary cutaneous lesions ( Jha et al., 2022 ); and iii) the treatment failure in the absence of DR ( Yardley et al., 2006 ). Longitudinal studies of infected individuals and monitoring of quiescence are needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 92%
“…The only report currently available on in-vivo quiescence in the context of chemotherapy revealed, in miltefosine-treated L. mexicana -infected BALB/c mice, the presence of quiescent amastigotes in collagen-rich, dermal mesothelium surrounding granulomas ( Kloehn et al., 2021 ): the authors concluded that quiescence, together with the lack of miltefosine accumulation in the mesothelium, may contribute to drug failure and non-sterile cure. The potential for DT and persistence shown here by L. braziliensis strains and by L. lainsoni ( Jara et al., 2022 ) might explain several (sub)clinical features associated with the species of subgenus Viannia , like i) the presence of parasites in 80% of scars, years after treatment with pentavalent antimony therapy ( Schubach et al., 1998 ); ii) the mucosal metastases from healed primary cutaneous lesions ( Jha et al., 2022 ); and iii) the treatment failure in the absence of DR ( Yardley et al., 2006 ). Longitudinal studies of infected individuals and monitoring of quiescence are needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 92%
“…IFC has been used to assess morphological changes occurring during promastigote to amastigote differentiation in L. donovani (64), to assess colocalisation of mCLING and lysotracker fluorescent stains in T. brucei (32) and to assess PI live/dead staining and for morphological measurements in L. mexicana (34). IFC has also been employed extensively to study host-parasite interactions for Leishmania and other intracellular pathogens) (19,(65)(66)(67)(68) as well as to detect Leishmania infections in blood and parasite dissemination to organs around the body (69). It has also been used to study trogocytosis by Entamoeba histolytica (70) and for drug screening in Plasmodium falciparum (71).…”
Section: Discussionmentioning
confidence: 99%
“…)clinical features associated with species of subgenus Viannia, like (i) the presence of parasites in 80% of scars, years after treatment with pentavalent antimony therapy (Schubach et al, 1998); (ii) the mucosal metastases from healed primary cutaneous lesions (Jha et al, 2022) and (iii) the treatment failure in absence of DR (Yardley et al, 2006). Longitudinal studies of infected individuals and monitoring of quiescence is needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%